(untitled) (Bangladesh Journal of Medical Science, 2023)
Primary hyperparathyroidism (PHPT) is a disease commonly seen in postmenopausal women. We report two cases of pathological fractures following trivial injuries in two different age groups; the middle and teen age group presented as PHPT due to parathyroid adenoma. PHPT usually presents with symptomatic hypercalcemia and target organ damage. Biochemical manifestations in both cases are similar i.e. hypercalcemia, elevated serum intact parathyroid hormone (iPTH), and mass in the parathyroid gland. Histopathological examination is consistent with parathyroid adenoma. We highlighted these two cases due to long delay before the PHPT diagnosisisconfirmedbecause of various investigations commenced in these patients to rule out other diagnoses. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 234-238